A basic study on the demand and problems face by micro-computer vendors / Noor Azlina Maarof - Maarof, Noor Azlina (1995)
This research is carried out as a partial fulfilment for the Diploma in Business Studies. The study is intended to provide a base from which micro-computer vendors, potential users and certain authorities can gain maximum benefit, in-line with the growth of the micro-computer industry in this country. Today, more than ever before, everybody is a potential user of a micro-computer. Therefore the major focus of this research has been, to present the demand in the micro-computer market, and the problems faced by micro-computer vendors in anticipation of the current demand. Chapter I explores the problems faced by micro-computer vendors briefly. In addition, technological development of micro-computer is also described. Among other things that were included in this chapter are the objectives, hypotheses, scope, limitation and assumption of the research. Chapter II deals with the review of literature which briefly describes the growth, demand, problems within the industry and the future prospect. This chapter also describes the vendor problems. Chapter III explains the methodology and approach and is followed by the findings in Chapter IV. Lastly Chapter V concludes the research and presents the recommendations with regards to the problems faced by the micro-computer vendors.